Toponimi Pantai Minanga sebagai Dasar Pariwisata Berkelanjutan - Rahmawaty Lamato; Sunarty Suly Eraku; Moch. Rio Pambudi (Universitas Negeri Gorontalo, 2026)
Minanga Beach in North Gorontalo has coastal tourism potential and a local name that reflects its geographic identity as a river mouth. This study aims to describe the origin and meaning of the Minanga toponym, analyze its relationship with coastal geographic aspects, and formulate directions for sustainable tourism development. The research used a descriptive qualitative approach through field observation, in-depth interviews with traditional leaders, community leaders, local government, tourism managers, and visitors, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, supported by source triangulation, technique triangulation, and member checking. The results show that Minanga in the Atinggola language refers to a river mouth or the meeting area of freshwater and seawater. The name is closely related to the beach landscape, river mouth, white sand, calm waters, coastal vegetation, hills, local history, and Safar bathing tradition. Toponymy can strengthen destination narratives, community participation, environmental awareness, and sustainable tourism planning.